A Design of Secondary School Web Portal for GuanTing Secondary School - Hui, Ma Cheng (2010)
Information technology and information communication technology play important role in the education areas. These facilities and techniques have been applied in secondary school spread to facilitate the teaching and learning process. Hence, the motive of the researching is to apply information technology into GuanTing senior school to facilitate the learning and teaching. The rapid application development called RAD methodology is applied in this project. The RAD includes those steps: analysis, design, build and test. The framework of GuanTing secondary school portal is established by reviewed literatures, current available school portals and the key features and functions based on the previous researcher. The GuanTing secondary school is design by Microsoft visual web developer and SQL 2005 server. That is running in the asp.net environment that provides high information security across using MD5 security technique. It is very grateful if this system would provide any additional helps for the GuanTing secondary school.